Morula cells and non-self recognition in the compound ascidian Botryllus schlosseri - L Ballarin; A Menin; N Franchi; G Bertoloni; F Cima (Invertebrate Survival Journal, 2005)
In the ascidian Botryllus schlosseri, we studied the effects of hemocyte incubation with foreigncells, such as bacteria, bacterial spores and yeast. In the presence of yeast and bacterial spores,morula cells, a common cell type in botryllid ascidians, changed their morphology, releasephenoloxidase in the medium, thus causing an increase in cytotoxicity, and express moleculesrecognised by anti-IL-1-a- and anti-TNF-a-antibodies. These effects were not observed whenhemocytes were incubated with both gram-positive (Staphylococcus aureus) and gram-negative(Escherichia coli) bacteria. Considering that morula cells are the main source of molecules recognisedby anti-cytokine-antibodies we suggest an immunosurveillance role of these cells, which may influenceimmune responses such as phagocytosis.